Fair Administrative Litigation in the Jurisprudence of the European Court of Human Rights - Radi, Mazen Lilo (Journal of Legal and Political Studies, 2015)
Administrative litigation is the legal mean by which all persons natural or legal protect their rights against administration and it consists of a number of process commences with bringing action before a court by plaintiff and it ends with a final verdict. This litigation often described as a dispute between public interest and a private interest due to the aim of each party of the litigation. The administration in such litigation is defendant most of times, due to the aspects of public power that enjoys and allows her to execute and implement her legal and substance work against the others directly. The defendant’s position in any litigation is easier than the position of the plaintiff according to the procedures law, because the final does not have any prerogative as the administrative, therefore the problem of inequality and imbalance between the two parties. This kind of situation requires searching for a fair administrative trail. The international convents and charts as well as the national laws and legislations aspire to achieve the fair trial before in the criminal courts in order to protect the defendant rights in imposing some limits and boundaries on the authorities of criminal justice and empowering the defendant to defend him. In the administration litigation the fair trail is signified in functioning appeal.
Keywords: Administrative litigation; plaintiff ,public power; interest